Developing a Clinical Decision Support Tool for Appropriate Antibiotic Prescribing in Australian General Practice: A Simulation Study. (May 2020) - Manski-Nankervis, Jo-Anne; Biezen, Ruby; Thursky, Karin; Boyle, Douglas; Clark, Malcolm; Lo, Sean; Buising, Kirsty
Background. Inappropriate antibiotic prescribing can lead to antimicrobial resistance and drug side effects. Tools that assist general practitioners (GPs) in prescribing decisions may help to optimize prescribing. The aim of this study was to explore the use, acceptability, and feasibility of a clinical decision support (CDS) tool that incorporates evidence-based guidelines and consumer information that integrates with the electronic medical record (EMR).Methods. Eight GPs completed an interview and brief survey after participating in 2 simulated consultations. The survey consisted of demographic questions, perception of realism and representativeness of consultations, Post-Study System Usability Questionnaire, and System Usability Scale. Qualitative data were analyzed using framework analysis. Video data were reviewed, with length of consultation and time spent using the CDS tool documented.Results. Survey responses indicated that all GPs thought the consultations were "real" and representative of real-life consultations; 7 of 8 GPs were satisfied with usability of the tool. Key qualitative findings included that the tool assisted with clinical decision making and informed appropriate antibiotic prescribing. Accessibility and ease of use, including content (guideline and patient education resources), layout, and format, were key factors that determined whether GPs said that they would access the tool in everyday practice. Integration of the tool at multiple sites within the EMR facilitated access to guidelines and assisted in ensuring that the tool fit the clinical workflow.Conclusion. Our CDS tool was acceptable to GPs. Key features required for the tool were easy navigation, clear and useful guideline content, ability to fit into the clinical workflow, and incorporation into the EMR. Piloting of the tool in general practices to assess the impact and feasibility of use in real-world consultations will now be undertaken.